Formas de alumínio em solo submetido a diferentes manejos e rotações de culturas - Wendling, Graziele Feltrin Dias (2012)
The use of different tillage systems and winter crop plants over a long period of time on a clayed and naturally acid soil can promote changes in the forms of aluminum present in the soil, reducing the possibility of its toxicity to major crops. The aim of this study was to evaluate different forms of aluminum in a Oxisol in an experiment conducted by IAPAR (Southwest of Paraná) for 23 years. In the region, which was originally covered by Atlantic Forest, two systems of tillage (no-tillage (NT) and Conventional Planting System (CPS) were employed using the cultivation of six different species of winter plants (lupine blue, hairy vetch, black oats, turnip, wheat and fallow) in sequence to soybean and corn in the summer. In October 2009, there was the collection of soil samples at five different depths (0-5, 5 -10, 10-20, 20-30 and 30-40 cm). The forms of aluminum present in the soil were determined using various extractants: ammonium oxalate and 0.2 M sodium dithionite, sodium bicarbonate, for forms of aluminum present in the mineral fraction of soil; 1M potassium chloride, for the exchangeable form of aluminum in the soil, copper chloride 0.5 M lanthanum chloride and 0.33 M for the aluminum complexed forms of the active sites of soil organic matter (MOS), and 0.1 M sodium pyrophosphate. Three different methods were used for determining the aluminum content in the extracts: titration with 0.0125 M NaOH followed by back titration, atomic absorption spectroscopy (AAS) and fluoride ion selective electrode (ESIF)*, and the three methods have presented limitations. In the assessment of the forms of Al in the soil under different tillage systems and with different crops in the rotation system the ESIF method was used for determination of the aluminum content in the different extracts. The use of a tillage that promotes the maintenance of soil organic matter and biomass of soil with cover crops and NT, did not lead to reduced availability of exchangeable aluminum in the soil, whose structure (mineral oxides and 1:1 iron and aluminum clay minerals ) and naturally acid pH, constitute a source of this element, which can be toxic to plants. Concentrations of non exchangeable aluminum (organically complexed) in the surface layers of soil were higher for the treatments with vetch, turnip and fallow in NT.